2011
DOI: 10.1111/j.1467-8667.2010.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified Genetic Algorithm for the Dynamic Identification of Structural Systems Using Incomplete Measurements

Abstract: A modified real-coded genetic algorithm to identify the parameters of large structural systems subject to the dynamic loads is presented in this article. The proposed algorithm utilizes several subpopulations and a migration operator with a ring topology is periodically performed to allow the interaction between them. For each subpopulation, a specialized medley of recent genetic operators (crossover and mutation) has been adopted and is briefly discussed. The final algorithm includes a novel operator based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
75
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 27 publications
0
75
0
Order By: Relevance
“…Accurate assessment of safety, however, is difficult, due to the analytical limitation and the fact that numerous assumptions must be made in the assessment process, considering the inherent uncertainties of large and complex civil structures. In this respect, in recent years many researchers have developed parametric system identification methods to estimate the structural parameters or non-parametric methods to estimate the structural response directly to be used in the analysis of the behavior of complex structures and determine their state of damage (Jiang and Adeli 2005;Adeli and Jiang 2006;Schoefs et al 2011;Marano et al 2011;Jafarkhani and Masri 2011;Sirca and Adeli 2012;Kang et al 2012;Hazra 2012;Yan and Ren 2012;Cho et al 2012;Fuggini et al 2013;Su et al, 2014). In addition, serviceability assessments using acceleration data require analysis of frequency and amplitude after measurements are completed making it difficult for the engineer to make a decision intuitively at the time of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Accurate assessment of safety, however, is difficult, due to the analytical limitation and the fact that numerous assumptions must be made in the assessment process, considering the inherent uncertainties of large and complex civil structures. In this respect, in recent years many researchers have developed parametric system identification methods to estimate the structural parameters or non-parametric methods to estimate the structural response directly to be used in the analysis of the behavior of complex structures and determine their state of damage (Jiang and Adeli 2005;Adeli and Jiang 2006;Schoefs et al 2011;Marano et al 2011;Jafarkhani and Masri 2011;Sirca and Adeli 2012;Kang et al 2012;Hazra 2012;Yan and Ren 2012;Cho et al 2012;Fuggini et al 2013;Su et al, 2014). In addition, serviceability assessments using acceleration data require analysis of frequency and amplitude after measurements are completed making it difficult for the engineer to make a decision intuitively at the time of measurement.…”
Section: Introductionmentioning
confidence: 99%
“…Jung et al (2010) used static measurements as damage index and multiobjective optimization as a search method for a 2-D simple truss structure. Marano et al (2011) proposed a modified single-objective GA to identify a 2-D structural system subjected to dynamic loads. Fuggini et al (2013) carried out system identification of retrofitting textile using inverse problem solving based on GAs.…”
Section: Introductionmentioning
confidence: 99%
“…This example proves that even regular inspections cannot guarantee structural Downloaded by [Univ Politec Cat], [Jose TURMO] at 00:39 15 June 2015 have any explicit physical meaning, which is their main drawback. During the last decades, computer development has enabled increasing popularity in non-parametric methods such as Neural Networks (Talebinejad et al 2011) or Genetic Algorithms (Marano et al 2011), as complex structural systems can be identified, whereas parametric methods have mainly been applied to very simple models, due to the complexity of the mathematical relations among the variables.…”
Section: Introductionmentioning
confidence: 99%